Restorative Justice: Customary Law Protecting Women's Rights and Upholding the Law - Wirawan, Rachmat; Komuna, Evelyn Pinkan (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2023)
Sexual violence against women is increasing every year, andthe long-standing and punishment-oriented  punishment of  perpetrators is still lacking in efforts to bring about justice for victims.  Aform of guarantee of protection for women appears restorative justice.  Inpractice, the restorative concept has not found its original form in the judicial litigation process in Indonesia. Responding to these challenges,  the concept of Indonesian customary criminal justice began to emerge. The enforcement of customary criminal law refers to togetherness and kinship, dispute resolution is through the agreement of all parties involved and based on expediency. The purpose of the application of customary criminals is to realize peace efforts to restore society to order in accordance with the feelings and awareness of the law that lives in the community.   This paper uses three approaches, namely, the conceptual approach,  the  historical approach and the hybrid legal system. From the results of the study, the application of customary criminal law is an alternative solution to protect women from acts of sexual violence. Indigenous criminal practices are in line with the spirit of restorative justice echoed by justice seekers.